Earnings Quality, Good Corporate Governance, Audit Quality and Firm Value: Moderated of Leverage - Sulyanto, Pranandang; Trisnawati, Estralita; Verawati, Verawati (SENTRALISASI, 2025)
The globalization era intensifies competition among companies, making firm value a crucial indicator of managerial performance and investor appeal. However, market shocks such as the COVID-19 pandemic and “stock pumping” phenomena reveal that firm value is not solely determined by fundamentals. This study aims to examine the effect of earnings quality, Good Corporate Governance, and audit quality on firm value, with leverage as a moderating variable. Specifically, the study seeks to assess how major internal and governance-related factors influence firm value during the pandemic period, a time marked by heightened uncertainty and volatility. The research uses a quantitative approach by employing panel data regression and moderated regression analysis with a fixed effect model on a sample of cyclical and non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The findings show that earnings quality has a positive impact on firm value, while GCG and audit quality do not have a significant impact. Moreover, leverage is found to weaken the influence of earnings quality on firm value, but does not moderate the relationship between GCG or audit quality and firm value. The study concludes that firm value is partially influenced by internal accounting quality and capital structure, yet these factors alone are insufficient to explain firm value volatility during turbulent market conditions. The implication of this study suggests that investors and policymakers should consider external and behavioral factors beyond traditional financial indicators when assessing firm value in a dynamic market environment.